2016
DOI: 10.1007/s40610-016-0036-4
|View full text |Cite
|
Sign up to set email alerts
|

Critical Sized Mandibular Defect Regeneration in Preclinical In Vivo Models

Abstract: Restoration of critical sized defects of the mandible still poses a major problem in the field of Oral and Maxillofacial Surgery. The current gold standard of treatment relies on the use of autologous grafts and therefore, has associated disadvantages such as donor site morbidity and insufficient bone for prosthetic rehabilitation. Recent advances in the fields of bone tissue engineering and distraction osteogenesis provide an alternative treatment modality to restore the aforementioned critical sized defects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…These defects actually represent a suitable model for evaluating the usefulness of treatments, because bone regeneration in critical-sized defects only occurs in the presence of osteogenic materials (32). Experimentally, it was found that the size of the CSD for the dog was 15 mm without periosteum (4,5,32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These defects actually represent a suitable model for evaluating the usefulness of treatments, because bone regeneration in critical-sized defects only occurs in the presence of osteogenic materials (32). Experimentally, it was found that the size of the CSD for the dog was 15 mm without periosteum (4,5,32).…”
Section: Discussionmentioning
confidence: 99%
“…Ideal mandibular reconstruction should restore form, function, sensation, mastication efficiency and esthetics (5). Autogenous bone grafting has always been the gold standard in reconstructing critical-sized bone defects; however, it has shown multiple disadvantages, such as increased patient morbidity, the limited volume of transported bone and the need for a second operative site (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reconstruction of CSD is a significant problem for Oral and Maxillofacial Surgeons because it will not heal spontaneously without intervention. It can regenerate>10 % of the lost bone during the patient's lifetime [2]. CSD heals predominantly with fibrous tissue, not bone because there are not enough bone-forming cells for bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…These defects primarily arise from tumor resection, infection, physical trauma, and osteomyelitis [2] . Such a critical defect will not heal on its own or regenerate more than 10% of the lost bone within the lifetime of the patient [3] . Not only is mandibular bone important for craniofacial aesthetics, but also for the support of muscles of mastication, facial expression and speech [4] .…”
Section: Introductionmentioning
confidence: 99%